Factors affecting people investing in Mutual Fund in Malaysia: An application of the Theory of Planned Behavior - Kuah, Kean Lam (2008)
Dana Bersama (Mutual Fund) di Malaysia mengalami perkembangan pesat dalam beberapa tahun yang lepas.